2018
DOI: 10.1002/adfm.201800342
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Versatile Pathway for the Synthesis of Visible Light Photoreactive Nanoparticles

Abstract: This work pioneers the design of visible (415 nm) and UV-B light (300 nm) reactive nanoparticles via radical polymerization in aqueous heterogeneous media based on methyl methacrylate (MMA) and unique acrylates bearing tetrazole functionalities in a simple and straightforward two step reaction. Stable colloidal nanoparticles with an average diameter of 150 nm and inherent tetrazole functionality (varying from 2.5 to 10 wt% relative to MMA) are prepared via one-pot miniemulsion polymerization. In a subsequent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…We subsequently evaluated the fluorescence of the particles and observed that the highest value is reached for 15 min of irradiation (Figure A, I max ). The subsequent decrease in fluorescence is most likely because of rearomatization of the pyrazoline (nonfluorescent adduct), as already described in literature. , Consequently, the CL output shows a similar trend as the light intensity is dependent on the fluorescent pyrazoline concentration (Figure B). SEM images after 15 min of irradiation showed polydisperse particles with small nuclei in the background, suggesting that the nucleation period is incomplete (Figures Cand S8).…”
Section: Results and Discussionsupporting
confidence: 76%
“…We subsequently evaluated the fluorescence of the particles and observed that the highest value is reached for 15 min of irradiation (Figure A, I max ). The subsequent decrease in fluorescence is most likely because of rearomatization of the pyrazoline (nonfluorescent adduct), as already described in literature. , Consequently, the CL output shows a similar trend as the light intensity is dependent on the fluorescent pyrazoline concentration (Figure B). SEM images after 15 min of irradiation showed polydisperse particles with small nuclei in the background, suggesting that the nucleation period is incomplete (Figures Cand S8).…”
Section: Results and Discussionsupporting
confidence: 76%
“…1 First described by Huisgen and Sustmann, 19 it has since been employed for a variety of applications, including protein labelling, 20 nucleic acid modification, 21 polymer ligation, 22 hydrogel assembly, 23 and modification of nanoparticles and microspheres. 24,25 In recent years, researchers have worked on extending the absorption profile of these compounds from UVB into the visible light regime, mostly by introducing substituents or extended conjugated chromophores at the N-phenyl ring. 22,26,27 However, to our knowledge, no NITEC reaction so far has been carried out with wavelengths longer than 420 nm in a one photon process.…”
mentioning
confidence: 99%
“…This reaction has been termed nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC) . The Tet compounds have been used in a number of chemical, biological, and materials applications . Importantly, they offer the inherent possibility to fine‐tune the activation wavelength by varying the structure of the aryl moieties .…”
Section: Methodsmentioning
confidence: 99%